Case Report: Refractory hidradenitis suppurativa complicated by IgA vasculitis with nephritis: successful long-term control with surgery and bimekizumab - Yasuda, Ayaka; Sasaki, Natsuko; Hasegawa, Emi; Sawada, Yu (Frontiers in Immunology, 2026)
Hidradenitis suppurativa (HS) is a chronic inflammatory skin disease that can rarely be complicated by systemic immune phenomena. We report a 41-year-old woman with severe HS refractory to adalimumab who developed fever, palpable purpura, and renal involvement. Skin biopsy confirmed IgA leukocytoclastic vasculitis, and renal biopsy revealed IgA nephritis. She was treated with corticosteroids, rituximab, and surgery, but proteinuria persisted. Initiation of bimekizumab led to marked improvement of HS lesions and a significant reduction in proteinuria. Over more than one year of follow-up, she achieved sustained HS control without recurrence of vasculitis or treatment-related adverse events. This case highlights the potential role of dual IL-17A/F inhibition in managing refractory HS complicated by IgA vasculitis and nephritis.